Mild Therapeutic Hypothermia Alters Hemostasis in ST Elevation Myocardial Infarction Patients - Scherz, Thomas; Hofbauer, Thomas M.; Ondracek, Anna S.; Simon, Daniel; Sterz, Fritz; Testori, Christoph; Lang, Irene M.; Mangold, Andreas (Frontiers in Cardiovascular Medicine, 2021)
Background and Rationale: Mild therapeutic hypothermia (MTH) is a concept to reduce infarct size and improve outcome after ST-segment elevation myocardial infarction (STEMI). In the STATIM trial, we investigated MTH as an additional therapy for STEMI patients. In the intention-to-treat set, 101 patients were included. No difference in primary and secondary endpoints measured by cardiac magnetic resonance imaging was found. Platelet activation and plasmatic coagulation are key in the pathophysiology of STEMI. In the present study, we investigated the effect of MTH on primary and secondary hemostasis in STEMI patients. Methods and Results: Platelet function and morphology were assessed by routine blood count, aggregometry testing, and flow cytometry. Soluble platelet markers were determined by enzyme-linked immunosorbent assay (ELISA) testing. Plasmatic coagulation was measured throughout the study. Platelet count remained unchanged, irrespective of treatment, whereas platelet size decreased in both patient groups. Platelet aggregometry indicated increased platelet reactivity in the MTH group. Furthermore, higher adenosine diphosphate (ADP) plasma levels were found in MTH patients. Expression of glycoprotein IIb/IIIa was increased on platelets of STEMI patients treated with MTH. Lower patient temperatures correlated with longer clotting times and resulted in reduced pH. Lower pH values were positively correlated with longer clotting times. Conclusion: Present data indicate longer clotting times and higher platelet reactivity in STEMI patients treated with MTH. These changes did not correspond to clinical bleeding events or larger infarct size.